Insights into the effect of halide enriched ZnO synthesized using tetrabutylammonium halides toward photocatalytic degradation of Rhodamine 6G. Issue 6 (2nd July 2021) - Satpal, Sudhakar B.; Athawale, Anjali A.
Abstract: ZnO and halide (Cl, Br, and I) enriched ZnO samples have been synthesized by polyol method. Halide enriched zinc oxide (ZnO‐X) were obtained when synthesis was carried out in the presence of tetrabutylammonium halide (X‐Cl, Br, and I) salts. X‐ray results reveal that the halide ions seem to occupy the oxygen vacancy sites as well as interstitial sites of the ZnO lattice increasing the cell volume and strain along the c‐axis. Microspheres are observed in the scanning electron micrographs with the size ranging between 170 and 385 nm. Photocatalytic activity of the synthesized samples was tested under UV light irradiation for the decomposition of Rhodamine‐6G dye. The halide enriched ZnO samples show higher rate of dye degradation compared to pristine ZnO attributable to their higher bandgap leading to a decrease in the recombination reactions of the electron–hole pair and higher light absorbing ability. ZnO‐Br is seen to exhibit the highest rate of degradation due to higher bandgap, light absorbing ability and predominance of (101) facet in the lattice. Further, ZnO‐Br appears to undergo negligible change after 3 cycles of catalysis proving its reusability.